The Suction Test: A Novel Technique to Identify and Verify Successful Repair of Peripheral Triangular Fibrocartilage Complex Tears - Greene, Ryan M.; Kakar, Sanjeev (Journal of Wrist Surgery, 2017)
Background The diagnoses of peripheral triangular fibrocartilage complex (TFCC) tears continue to be the subject of numerous investigations.Case Description We describe a novel arthroscopic technique that may be used as an adjunct with other arthroscopic maneuvers to diagnose and confirm repair of peripheral sided TFCC injuries.Literature Review The hook and trampoline tests are intraoperative techniques to diagnose TFCC tears.Clinical Relevance The suction test provides a means to detect peripheral tears and to confirm restoration of its tension post repair.
Keywords: peripheral triangular fibrocartilage complex tears; TFCC; suction test; wrist